Genetic variants associated with angiotensin-converting enzyme inhibitor-induced cough: a genome-wide association study in a Swedish population. (February 2017) - Hallberg, Pär; Persson, Matilda; Axelsson, Tomas; Cavalli, Marco; Norling, Pia; Johansson, Hans-Erik; Yue, Qun-Ying; Magnusson, Patrik KE; Wadelius, Claes; Eriksson, Niclas; Wadelius, Mia
Aim: We conducted a genome-wide association study on angiotensin-converting enzyme inhibitor-induced cough and used our dataset to replicate candidate genes identified in previous studies.Patients & methods : A total of 124 patients and 1345 treated controls were genotyped using Illumina arrays. The genome-wide significance level was set to p < 5 × 10 -8 .Results : We identified nearly genome-wide significant associations in CLASP1, PDE11A, KCNMB2, TGFA, SLC38A6 and MMP16 . The strongest association was with rs62151109 in CLASP1 (odds ratio: 3.97; p = 9.44 × 10 -8 ). All top hits except two were located in intronic or noncoding DNA regions. None of the candidate genes were significantly associated in our study.Conclusion : Angiotensin-converting enzyme inhibitor-induced cough is potentially associated with genes that are independent of bradykinin pathways.